AB0929 THE IMPACT OF KINESIOPHOBIA ON GAIT KINEMATICS IN PATIENTS WITH SPONDYLOARTHROPATHIES - Schweiger, Isabella; Koschinsky, J.; Godonou, Elie-Tino; Tascilar, Koray; Coppers, Birte; Kleyer, Arnd; Morf, Harriet; Simon, David; Bayat, Sara; Bohr, Daniela; Valor, L.; Raimondo, Maria Gabriella; et al. (Annals of the Rheumatic Diseases, 2024)
Background: In light of much needed functional assessments to monitor disease activity and functional status in spondyloarthritis (SpA), gait analysis is gaining interest. While it is generally known that the functional status and gait kinematics are closely related, it is unclear how fear of movement (kinesiophobia) affects gait kinematics in SpA patients. Objectives: To assess the influence of kinesiophobia on gait kinematics in patients with SpA and how sex mediates this relationship. Methods: A standardized 2-minute walk with self-selected walking speed was performed with 104 patients (psoriatic arthritis (PsA, CASPAR criteria) and ankylosing spondylitis (axSpa, ASAS criteria) (Internal Medicine 3 outpatient clinics Erlangen, Germany) in the hospital hallway. Spatio-temporal gait parameters (number of analyzed steps, cadence, gait velocity, double stance length and duration, swing left and right, stance left and right, temporal and spatial gait cycle variability) were recorded using the inertial sensor system RehaGait® (Hasomed, Magdeburg, Germany) and sagittal joint angles were computed and analyzed via MATLAB [1] (of the whole gait cycle the maximal and minimal flexion angle of left and right hip, knee, ankle). Patient characteristics and clinical assessments were retrieved from the patients record on the day of the gait analysis. Additionally, patients were asked to fill out the tampa scale of kinesiophobia (TSK) and an anamnestic questionnaire. Multivariate multiple linear regression was used to investigate the relationship between TSK score and kinematic gait parameters; mediation analysis was computed with sex as the control variable (potential mediator). Results: Patients characteristics of the 104 participants in this study are summarized in Table 1. Kinesiophobia affected the mediator sex (0.039; CI (0.005, 0.074), p=0.026) and the effect of kinesiophobia on gait kinematics differs between sexes. When controlling for the TSK score, male subjects took fewer steps and had a longer stance length. This may be due to them being taller (female: 166.6 cm, male: 179.9 cm; p<0.001). When controlling for sex, kinesiophobia is significantly associated with gait velocity (Coef: -0.009, p=0.003), double stance length (Coef: -0.005, p=0.031), double stance duration (Coef: 0.004, p=0.007), cadence (Coef: -0.39, p=0.006), swing phase left (Coef: -0.089, p=0.006) and the minimal left knee angle (Coef: -0.002, p=0.046). Conclusion: Patients with higher fear of movement scores by TSK walked slower, had a lower cadence, took smaller steps and had an increased extension of the left knee. While previous studies [2, 3] reported a decreased range of motion in axSpa patients compared to healthy subjects our results suggest that this can not only result from disease status itself, but that gait kinematics are associated with fear of movement. This is important to consider when gait analysis is used to assess the effect of interventions on functional status in SpA patient

AB0930 Towards Objective Measurement Of Spinal Mobility In Axial Spondyloarthritis – Benchmarking An Inertial Measurement Unit System With An Optical Measurement System - Blazek, V.; Loy, N.; Jukic, Elke; Coppers, Birte; Fleischmann, Martha Elisa; Hübner, Julian; Iqbal, M.; Heinrich, Simon; Scheiterer, Eduard; Leyendecker, Sigrid; Greenfield, Julia; Labinski, H.; et al. (Annals of the Rheumatic Diseases, 2024)

Accelerating AxSpA Diagnosis: Exploring At-home Self-sampling, Symptom Checkers, Medical Student-visits and Asynchronous Reportbased Assessment - Labinsky, Hannah; Von Rohr, Sophie; Raimondo, Maria Gabriella; Vogt, Ekaterina; Horstmann, Britta; Gehring, Isabel; Rojas-Restrepo, Jessica; Proft, Fabian; Muehlensiepen, Felix; Bohr, Daniela; Schett, Georg; Ramming, Andreas; et al. (ARTHRITIS & RHEUMATOLOGY, 2022)
CRIS-Team WoS Importer:2023-01-13

A MINIMAL-INVASIVE METHOD TO RETRIEVE AND IDENTIFY ENTHESEAL TISSUE FROM PSORIATIC ARTHRITIS PATIENTS - Raimondo, Maria Gabriella; Pachowsky, Milena; Xu, Cong; Rauber, Simon; Tascilar, Koray; Labinsky, Hannah; Soare, A.; Bräuer, Lars; Rech, Jürgen; Simon, David; Kleyer, Arnd; Schett, Georg; et al. (ANNALS OF THE RHEUMATIC DISEASES, 2022)
CRIS-Team WoS Importer:2022-11-04

Anatomical pattern of entheseal and synovial fibroblast activation in patients with psoriasis and its risk of developing psoriatic arthritis - Corte, Giulia; Atzinger, Armin; Temiz, Selahattin Alp; Noversa de Sousa, Rita; Mutlu, Melek Yalcin; Schönau, Verena; Raimondo, Maria Gabriella; Kleyer, Arnd; Kuwert, Torsten; Ramming, Andreas; Simon, David; Sticherling, Michael; et al. (RMD Open, 2024)
OBJECTIVES: To assess the presence and anatomical distribution of activated fibroblasts in the joints and entheses of patients with psoriasis with arthralgia and to test how fibroblast activation visualised by 68gallium-labelled fibroblast activation protein inhibitor-04 (68Ga-FAPI-04)-positron emission tomography (PET)/CT correlates with clinical tenderness, musculoskeletal ultrasound findings and progression to psoriatic arthritis (PsA). METHODS: We conducted a prospective cohort study in patients with psoriasis and arthralgia who underwent clinical and ultrasound evaluation and whole-body PET/CT imaging with 68Ga-FAPI-04. 68Ga-FAPI-04 uptake at synovial and entheseal sites was assessed by maximal standardised uptake values (SUVmax) and PET/CT Joint Index (JI); logistic regression models were used to investigate its correlation with clinical and ultrasound findings. Survival analyses were performed on patients with at least 6 months of follow-up. RESULTS: 36 patients with psoriasis were enrolled. 68Ga-FAPI-04 uptake was found in 318 (7.9%) joints and 369 (7.3%) entheses in 29 (80.6%) participants, with a mean SUVmax (SD) of 3.2 (1.8) for joints and 2.9 (1.6) for entheses. Large joints and the lower limbs were predominantly affected. A significant positive relationship was found between 68Ga-FAPI-04-PET/CT signal intensity and the 68 tender joint count (SUVmax: p<0.001; PET/CT-JI: p<0.001) and tender entheses count (SUVmax: p<0.001; PET/CT-JI: p=0.002). No correlations were found with ultrasound findings (SUVmax: p=0.969; PET/CT-JI: p=0.720). Patients with relevant synovio-entheseal 68Ga-FAPI-04 uptake showed a statistically significant higher risk of developing PsA (p=0.02), independent of ultrasound findings. CONCLUSIONS: Patients with psoriasis presenting with arthralgia show localised signs of resident tissue activation in joints and entheses, which are associated with higher risk of developing PsA.
CRIS-Team Scopus Importer:2024-06-21
Keywords: Fibroblasts; Outcome Assessment; Health Care; Psoriatic Arthritis; Risk Factors; Ultrasonography

APP-BASED (DIGA) BACK PAIN TREATMENT IN PATIENTS WITH AXIAL SPONDYLOARTHRITIS: RESULTS OF A RANDOMIZED CONTROLLED TRIAL - Palm von Alten Blaskowitz, Paloma Alexandra; Liphardt, Anna-Maria; Coppers, Birte; Bouzas Catalano, Claudia; Bundle, Vanessa; Rudolf, Sebastian; Knitza, Johannes; Raimondo, Maria Gabriella; Labinsky, Hannah; Hatscher, L; Wirsching, Andreas; Bohr, Daniela; et al. (Annals of the Rheumatic Diseases, 2024)

BCMA CAR T cells in a patient with relapsing idiopathic inflammatory myositis after initial and repeat therapy with CD19 CAR T cells - Müller, Fabian; Wirsching, Andreas; Hagen, Melanie; Völkl, Simon; Tur, Carlo; Raimondo, Maria Gabriella; Taubmann, Jule; Bucci, Laura; Zhang, Liang; Kretschmann, Sascha; Aigner, Michael; Eckstein, Markus; et al. (Nature Medicine, 2025)
CD19 chimeric antigen receptor (CD19 CAR) T cell therapy has been shown to induce stable drug-free remission in patients with refractory autoimmune disease. The management of potential relapses is currently unclear. Here we report on a 45-year-old woman with treatment-refractory Jo-1-associated anti-synthetase syndrome, who initially achieved disease remission after CD19 CAR T cell therapy but then experienced disease relapse after 9 months. After reinfusion of the same product, CAR T cells failed to expand and T cells targeting the CD19 CAR were detected. Despite full-dose lymphodepletion, no clinical response was observed. After bridging with anti-CD38 antibody daratumumab, which was efficacious with limited durability, plasma-cell-targeting B-cell maturation antigen (BCMA) CAR T cell therapy was performed. BCMA CAR T cells expanded, cleared plasma cells in lymphoid tissue, reduced autoantibody levels and re-induced stable drug-free remission. This case highlights the challenges in CAR T cell reinfusion, the potential of alternative targets and products, and suggests that the depletion of plasma cells may enhance therapeutic outcomes in patients who become treatment-refractory.
CRIS-Team Scopus Importer:2025-05-23

BCMA-Targeted T-Cell-Engager Therapy for Autoimmune Disease. - Hagen, Melanie; Bucci, Laura; Böltz, Sebastian; Nöthling, Danae-Mona; Rothe, Tobias; Anoshkin, Kirill; Raimondo, Maria Gabriella; Tur, Carlo; Wirsching, Andreas; Wacker, Jochen; Düsing, Christina; Distler, Jörg H.W.; et al. (New England Journal of Medicine, 2024)
EVALuna2:593855

Bispecific T cell engager therapy for refractory rheumatoid arthritis - Bucci, Laura; Hagen, Melanie; Rothe, Tobias; Raimondo, Maria Gabriella; Fagni, Filippo; Tur, Carlo; Wirsching, Andreas; Wacker, Jochen; Wilhelm, Artur; Auger, Jean-Philippe; Pachowsky, Milena; Eckstein, Markus; et al. (Nature Medicine, 2024)
Bispecific T cell engagers (BiTEs) kill B cells by engaging T cells. BiTEs are highly effective in acute lymphoblastic leukemia. Here we treated six patients with multidrug-resistant rheumatoid arthritis (RA) with the CD19xCD3 BiTE blinatumomab under compassionate use. Low doses of blinatumomab led to B cell depletion and concomitant decrease of T cells, documenting their engager function. Treatment was safe, with brief increase in body temperature and acute phase proteins during first infusion but no signs of clinically relevant cytokine-release syndrome. Blinatumomab led to a rapid decline in RA clinical disease activity in all patients, improved synovitis in ultrasound and FAPI-PET-CT and reduced autoantibodies. High-dimensional flow cytometry analysis of B cells documented an immune reset with depletion of activated memory B cells, which were replaced by nonclass-switched IgD-positive naïve B cells. Together, these data suggest the feasibility and potential for BiTEs to treat RA. This approach warrants further exploration on other B-cell-mediated autoimmune diseases.
CRIS-Team Scopus Importer:2024-05-03

CD19-CAR T-cell therapy induces deep tissue depletion of B cells - Tur, Carlo; Eckstein, Markus; Velden, Joachim; Rauber, Simon; Bergmann, Christina; Auth, Janina; Bucci, Laura; Corte, Giulia; Hagen, Melanie; Wirsching, Andreas; Grieshaber Bouyer, Ricardo; Reis, Petra; et al. (Annals of the Rheumatic Diseases, 2024)
Objectives CD19-targeting chimeric antigen receptor (CAR) T-cell therapy can induce long-term drug-free remission in patients with autoimmune diseases (AIDs). The efficacy of CD19-CAR T-cell therapy is presumably based on deep tissue depletion of B cells; however, such effect has not been proven in humans in vivo. Methods Sequential ultrasound-guided inguinal lymph node biopsies were performed at baseline and after CD19-CAR T-cell therapy in patients with AIDs. Results were compared with lymph node biopsies from rituximab (RTX)-treated AID patients with absence of peripheral B cells. Conventional and immunohistochemistry staining were performed on lymph node tissue to assess architecture as well the number of B cells, follicular dendritic cells (FDCs), plasma cells, T cells and macrophages. Results Sequential lymph node biopsies were analysed from five patients with AID before and after CD19-CAR T-cell therapy and from five patients with AID after RTX treatment. In addition, non-lymphoid organ biopsies (colon, kidney and gallbladder) from three additional patients with AID after CD19-CAR T-cell therapy were analysed. CD19+ and CD20+ B cells were completely depleted in the lymph nodes after CD19-CAR T-cell therapy, but not after RTX treatment. Plasma cells, T cells and macrophages in the lymph nodes remained unchanged. Follicular structures were disrupted and FDCs were depleted in the lymph nodes after CD19-CAR T-cell therapy, but not after RTX. Non-lymphoid organs were completely depleted of B cells. Discussion This study demonstrates complete B-cell depletion in secondary lymphoid tissues of patients with AIDs following CD19-CAR T-cell therapy combined with standard lymphodepleting therapy.
CRIS-Team Scopus Importer:2024-09-27
Keywords: Autoimmune Diseases; B-Lymphocytes; Rituximab; Ultrasonography

CD19-targeting CAR T-cell therapy in patients with diffuse systemic sclerosis: a case series - Auth, Janina; Müller, Fabian; Völkl, Simon; Bayerl, Nadine; Distler, Jörg H.W.; Tur, Carlo; Raimondo, Maria Gabriella; Chenguiti Fakhouri, Sara; Atzinger, Armin; Coppers, Birte; Eckstein, Markus; Liphardt, Anna-Maria; et al. (The Lancet Rheumatology, 2024)
Background: CD19-targeting chimeric antigen receptor (CAR) T-cell therapy has shown remarkable outcomes in patients with systemic lupus erythematosus. The effects of CD19-targeting CAR T cells on organ manifestations in patients with systemic sclerosis have yet to be characterised. B cells have a central role in the pathogenesis of systemic sclerosis. We present a detailed analysis of the effects of CD19-targeting CAR T-cell therapy in patients with systemic sclerosis. Methods: Six patients with severe diffuse systemic sclerosis with an insufficient response to at least two treatments were consecutively recruited at the Department of Internal Medicine 3, University Hospital Erlangen (Erlangen, Germany) to receive CD19-targeting CAR T-cell treatment (1 × 106 CAR T cells per kg bodyweight). Events were predefined by progression of interstitial lung disease, onset of congestive heart failure, onset of renal failure, onset of arterial hypertension, or initiation of new immunosuppressive or antifibrotic therapy. Event-free time or treatment intensification after study entry was the primary outcome. Key secondary outcomes included changes in the modified Rodnan Skin Score (mRSS), imaging (a component of the assessment of lung fibrosis), laboratory assessments, patient-reported outcomes, and a modified version of the American College of Rheumatology Composite Response Index in Systemic Sclerosis (ACR-CRISS), assessed at baseline, 3 months, 6 months, 9 months, and 12 months. Findings: Between April 20, 2022, and Nov 8, 2023, six patients with severe diffuse systemic sclerosis (median age 42 years [IQR 36–53]; four men and two women; all White European) were recruited and received CD19-targeted CAR T-cell therapy. The median follow-up time was 487 days (IQR 342–585). No events occurred within the observational period. Probability of improvement in the ACR-CRISS score increased to a median of 100% (IQR 100–100) at 6 months. Median mRSS decreased by 31% (IQR 29–38), corresponding to a median of 8 points (IQR 7–13) within 100 days. The extent of disease on CT scan decreased by a median of 4% (IQR 3–4) due to reduction of ground-glass opacities while the reticular pattern remained stable. Forced vital capacity improved by a median of 195 mL (IQR 18–275) at the latest observational timepoint. Interpretation: We provide the first evidence that CD19-targeting CAR T-cell therapy might intercept with the progression of fibrotic organ manifestations in patients with systemic sclerosis. Funding: Deutsche Forschungsgemeinschaft, Deutsche Krebshilfe, ELAN-Foundation Erlangen, IZKF Erlangen, and Bundesministerium für Bildung und Forschung.
CRIS-Team Scopus Importer:2024-12-13

CD200+ fibroblasts form a pro-resolving mesenchymal network in arthritis - Rauber, Simon; Mohammadian, Hashem; Schmidkonz, Christian; Atzinger, Armin; Soare, Alina; Treutlein, Christoph; Kemble, Samuel; Mahony, Christopher B.; Geisthoff, Manuel; Angeli, Mario Raphael; Raimondo, Maria Gabriella; Xu, Cong; et al. (Nature Immunology, 2024)
Fibroblasts are important regulators of inflammation, but whether fibroblasts change phenotype during resolution of inflammation is not clear. Here we use positron emission tomography to detect fibroblast activation protein (FAP) as a means to visualize fibroblast activation in vivo during inflammation in humans. While tracer accumulation is high in active arthritis, it decreases after tumor necrosis factor and interleukin-17A inhibition. Biopsy-based single-cell RNA-sequencing analyses in experimental arthritis show that FAP signal reduction reflects a phenotypic switch from pro-inflammatory MMP3+/IL6+ fibroblasts (high FAP internalization) to pro-resolving CD200+DKK3+ fibroblasts (low FAP internalization). Spatial transcriptomics of human joints indicates that pro-resolving niches of CD200+DKK3+ fibroblasts cluster with type 2 innate lymphoid cells, whereas MMP3+/IL6+ fibroblasts colocalize with inflammatory immune cells. CD200+DKK3+ fibroblasts stabilized the type 2 innate lymphoid cell phenotype and induced resolution of arthritis via CD200–CD200R1 signaling. Taken together, these data suggest a dynamic molecular regulation of the mesenchymal compartment during resolution of inflammation.
Created from Fastlane, Scopus look-up

Concise report: a minimal-invasive method to retrieve and identify entheseal tissue from psoriatic arthritis patients - Pachowsky, Milena; Raimondo, Maria Gabriella; Xu, Cong; Rauber, Simon; Tascilar, Koray; Labinsky, Hannah; Vogg, Mario; Saad, Mina saad aziz; Simon, David; Rech, Jürgen; Soare, Alina; Bräuer, Lars; et al. (Annals of the Rheumatic Diseases, 2022)
Objectives To establish a minimally invasive biopsy technique for the analysis of entheseal tissue in patients with psoriatic arthritis (PsA). Methods Human cadavers were used for establishing the technique to retrieve tissue from the lateral humeral epicondyle enthesis (cadaveric biopsies). After biopsy, the entire enthesis was surgically resected (cadaveric resections). Biopsies and resections were assessed by label-free second harmonic generation (SHG) microscopy. The same technique was then applied in patients with PsA with definition of entheseal tissue by SHG, staining of CD45+immune cells and RNA extraction. Results Entheseal biopsies from five cadavers allowed the retrieval of entheseal tissue as validated by the analysis of resection material. Microscopy of biopsy and resection sections allowed differentiation of entheseal, tendon and muscle tissue by SHG and definition of specific intensity thresholds for entheseal tissue. In subsequent entheseal biopsies of 10 PsA patients: the fraction of entheseal tissue was high (65%) and comparable to cadaveric biopsies (68%) as assessed by SHG microscopy. Furthermore, PsA biopsies showed immune cell infiltration and sufficient retrieval of RNA for further molecular analysis. Conclusion Entheseal biopsy of the lateral epicondyle is feasible in patients with PsA allowing reliable retrieval of entheseal tissue and its identification by SHG microscopy.
CRIS-Team WoS Importer:2022-05-13

Effects of different B-cell-depleting strategies on the lymphatic tissue - Tur, Carlo; Eckstein, Markus; Bucci, Laura; Auth, Janina; Bergmann, Christina; Rauber, Simon; Hagen, Melanie; Nöthling, Danae-Mona; Böltz, Sebastian; Wirsching, Andreas; Tascilar, Koray; Fagni, Filippo; et al. (Annals of the Rheumatic Diseases, 2025)
Objectives: To assess the efficacy of new protein-based B cell depletion with glyco-engineered anti-CD20 antibody obinutuzumab (OBI) and the CD19/CD3 T cell engager blinatumomab (BLI) in patients with autoimmune diseases (AIDs) in comparison to rituximab (RTX) and CD19 chimeric antigen receptor (CAR) T cell therapy. Methods: Sequential inguinal lymph node biopsies were taken before and after treatment with OBI-, BLI-, RTX- and CD19-CAR T cells in patients with AID. CD19+ and CD20+ B cells, plasma cells, T cells and macrophages were analysed by immunohistochemistry. Changes in follicular architecture (follicular dendritic cells, T follicular helper cells, proliferation) were also assessed. Results: Baseline and follow-up lymph node biopsies from 24 patients with AID (OBI, 4; BLI, 4; RTX, 4; CD19-CAR T cells, 12) were analysed. B cell depletion was confirmed in all CD19-CAR T cell-treated patients but only in 1 (OBI) out of 12 protein-based B cell-treated patients. Likewise, follicular architecture was disrupted in all CD19-CAR T cell-treated patients but only in 1 (OBI) out of 12 protein-based B cell-treated patients. B cell depletion efficacy in the lymph nodes was 100% for CD19-CAR T cells, 92% for OBI, 86% for RTX and 69% for BLI. Plasma cells were reduced but not depleted in all treatment approaches. CD3+ T cells and CD68+ macrophages remained unaffected. Peripheral blood B cell depletion occurred in all but 1 BLI-treated patient. B cell depletion was associated with stable drug-free remission, whereas a reduction in B cell numbers without depletion required retreatment with immunomodulatory drugs. Conclusions: Protein-based B cell depletion reduces but usually does not deplete B cells in lymph nodes leaving the follicular architecture intact and being associated with disease recurrence.
CRIS-Team Scopus Importer:2025-07-18

Entheseal Biopsy Approach: An Ultrasound-guided Method for Retrieval of Entheseal Tissue from Psoriatic Arthritis Patients - Raimondo, Maria Gabriella; Pachowsky, Milena; Xu, Cong; Rauber, Simon; Tascilar, Koray; Labinsky, Hannah; Vogg, Mario; Saad, Mina saad aziz; Simon, David; Rech, Jürgen; Soare, Alina; Bräuer, Lars; et al. (ARTHRITIS & RHEUMATOLOGY, 2022)
CRIS-Team WoS Importer:2023-01-13

Entheseal tissue signature in response to IL-17A inhibition in psoriatic arthritis: results from the EBIO entheseal biopsy study - Raimondo, Maria Gabriella; Mohammadian, Hashem; Rauber, Simon; Alivernini, Stefano; Fedorchenko, Vladyslav; Rigau, Aleix Rius; Angeli, Mario Raphael; Fagni, Filippo; Corte, Giulia; Tascilar, Koray; Labinsky, Hannah; Ramming, Alina; et al. (Annals of the Rheumatic Diseases, 2025)
Objectives: Enthesitis, a hallmark of psoriatic arthritis (PsA), reflects the interplay between mechanical stress and immune dysregulation at tendon-bone interfaces. This study investigates the cellular and molecular responses in entheseal tissues following interleukin (IL)-17A inhibition in patients with active PsA. Methods: In this prospective, interventional phase 4 trial, we enrolled 10 patients with enthesitis of the lateral epicondyle, performed entheseal biopsies, and analysed tissues by imaging mass cytometry (IMC) and spatial transcriptomics before and after treatment. Results: Following 24 weeks of IL-17A inhibition, 9/10 patients of the cohort clinically responded to treatment as assessed by Disease Activity in Psoriatic Arthritis (DAPSA), Spondyloarthritis research consortium of canada (SPARCC) score, and power Doppler sonography. IMC analysis showed significant reductions of enthesitis-related immune cell populations, in particular IL-17-producing CD4, CD8, CD4neg/CD8negT cells, granulocytes, and innate lymphoid cells type 3. Spatial transcriptomics revealed that CD200+DKK3+ fibroblasts and innate lymphoid cells type 2 expanded and formed an anti-inflammatory niche upon treatment. Notably, IL-17A inhibition led to decreased osteoblast differentiation markers, suggesting a potential mechanism to inhibit pathological bone formation. Conclusions: These findings underline the pivotal role of IL-17A in enthesitis, showing that IL-17A inhibition profoundly modulates the tissue microenvironment of entheses in PsA.
CRIS-Team Scopus Importer:2025-11-07

Fibroblast Activation Protein (FAP)-Mediated Cleavage of Type III Collagen Reveals Serum Biomarker Potential in Non-Small Cell Lung Cancer and Spondyloarthritis - Pedersen, Rasmus S.; Thorlacius-Ussing, Jeppe; Raimondo, Maria Gabriella; Langholm, Lasse L.; Schett, Georg; Ramming, Andreas; Karsdal, Morten; Willumsen, Nicholas (Biomedicines, 2024)
Fibroblast activation protein (FAP) is a known promoter of tumor development and is associated with poor clinical outcome for various cancer types. Being specifically expressed in pathological conditions including multiple types of fibrosis and cancers, FAP is an optimal target for diagnostics and treatment. Treatment strategies utilizing the unique proteolytic activity of FAP are emerging, thus emphasizing the importance of biomarkers to directly assess FAP activity. FAP is a type II transmembrane serine protease that has been shown to cleave collagens and other ECM components. In this study, we developed an ELISA assay (C3F) targeting a circulating type III collagen fragment derived from FAP cleavage to reflect FAP activity. We demonstrated that C3F was specific to the neoepitope of the cleavage site and that the fragment was generated through FAP cleavage of type III collagen. We measured C3F in serum from a cohort of patients with non-small cell lung cancer (NSCLC) (n = 109) matched to healthy subjects (n = 42) and a cohort of patients with spondyloarthritis (SpA) (n = 17) matched to healthy subjects (n = 19). We found that C3F was significantly elevated in patients with NSCLC and in patients with SpA compared to healthy controls (p < 0.0001 and p = 0.0015, respectively). These findings suggest that C3F is a promising non-invasive biomarker reflecting FAP activity, which may aid in understanding tumor heterogeneity and potentially FAP-targeted therapies.
CRIS-Team Scopus Importer:2024-04-05
Keywords: extracellular matrix remodeling; fibroblast activation protein (FAP); non-small cell lung cancer (NSCLC); serum biomarker; spondyloarthritis

Fibroblast Activation Protein (FAP) PET-CT for Depicting Inflammatory Joint Damage in Patients with Psoriatic Arthritis - Rauber, Simon; Mohammadian, Hashem; Schmidkonz, Christian; Atzinger, Armin; Raimondo, Maria Gabriella; Labinsky, Hannah; Treutlein, Christoph; Knitza, Johannes; Maschauer, Simone; Roemer, Frank; Prante, Olaf; Kuwert, Torsten; et al. (ARTHRITIS & RHEUMATOLOGY, 2022)
CRIS-Team WoS Importer:2023-01-13

FIBROBLAST ACTIVATION PROTEIN (FAP) PET-CT IMAGING ALLOWS TO DEPICT INFLAMMATORY JOINT REMODELING IN PATIENTS WITH PSORIATIC ARTHRITIS - Schmidkonz, Christian; Rauber, Simon; Raimondo, Maria Gabriella; Labinsky, Hannah; Atzinger, Armin; Treutlein, Christoph; Knitza, Johannes; Maschauer, Simone; Roemer, Frank; Prante, Olaf; Kuwert, Torsten; Canete, J. D. D.; et al. (ANNALS OF THE RHEUMATIC DISEASES, 2022)
CRIS-Team WoS Importer:2022-11-04

Impact of the digital health application ViViRA on spinal mobility, physical function, quality of life and pain perception in spondyloarthritides patients: a randomized controlled trial - Palm von Alten Blaskowitz, Paloma Alexandra; Liphardt, Anna-Maria; Bouzas, Claudia; Coppers, Birte; Petit, Pascal; Vuillerme, Nicolas; Bundle, Vanessa; Rudolf, Sebastian; Knitza, Johannes; Raimondo, Maria Gabriella; Labinsky, Hannah; Hatscher, Lukas; et al. (Arthritis Research & Therapy, 2024)
Background: Spondyloarthritides (SpAs) are a group of common rheumatic diseases that often cause limited mobility and lower back pain. Physiotherapy is an integral part of treatment, but access to physiotherapy limits treatment success. Digital health applications (DHAs) enable home-based physiotherapy and could significantly improve access for SpAs patients. The aim is to investigate the clinical effects of the DHA ViViRA compared with those of standard physiotherapy. Methods: SpAs patients with chronic back pain were enrolled in a randomized controlled trial. The intervention group received ViViRA DHA, whereas the control group received standard physiotherapy. Pain (verbal rating scale, PAIN-Detect), quality of life (SF-36) and mobility (BASMI) were assessed at baseline and after 12 weeks as the primary outcomes. Results: Data from 59 participants (71.2% female, mean age 45.2 years) were analyzed. The intervention group showed a significant improvement in mobility (average BASMI score: baseline: 1.1 [range 0.7–1.5]; follow-up: 1.0 [range 0.5–1.4]; p = 0.05), whereas the control group showed a significant decrease in mobility (baseline: 1.5 [range 1.1–1.9]; follow-up: 1.8 [range 1.4–2.2]; p = 0.00). The intervention group demonstrated lower pain intensity (VRS pain level at week 3.5 ± 2.8) than did the control group (VRS pain level at week 4.5 ± 2) after 12 weeks. Conclusion: Our results highlight the efficacy of DHAs such as ViViRA in the treatment of lower back pain in SpAs patients. Compared with the current gold standard, physiotherapy, DHA use results in superior outcomes. However, further larger studies are needed to confirm these promising results. Trial registration: The study is registered in the German clinical trial registry (DRKS) under the following ID: DRKS00031254.
CRIS-Team Scopus Importer:2025-02-04
Keywords: DHA; Digital health application; E-Health; Mobility; Physical function; Psoriatic spondylitis; Spondyloarthritides; Spondyloarthropathy; ViViRA

JAK Inhibition Re-balances Gene Expression Profile of Circulating Immune Cells in Patients with Psoriatic Arthritis - Raimondo, Maria Gabriella; Anchang, Charles Gwellem; Labinsky, Hannah; Saad, Mina saad aziz; Rauber, Simon; Vogg, Mario; Kampylafka, Eleni; Knitza, Johannes; Soare, Alina; Schett, Georg; Ramming, Andreas (ARTHRITIS & RHEUMATOLOGY, 2022)
CRIS-Team WoS Importer:2023-01-13

Matrix stiffness regulates profibrotic fibroblast differentiation and fibrotic niche activation in systemic sclerosis - Ueberall, Ludwig; Mohammadian, Hashem; Demmler, Richard; Ariza, Yuko; Tripal, Philipp; Anchang, Charles Gwellem; Weber, Stefanie; Angeli, Mario Raphael; Raimondo, Maria Gabriella; Chang, Jiyang; Huang, Kaiyue; Distler, Jörg H.W.; et al. (Annals of the Rheumatic Diseases, 2025)
Objectives: Fibrosis progression in systemic sclerosis (SSc) has been attributed to matrix stiffness. Despite extensive research on fibroblast heterogeneity and subset imbalances in fibrotic disorders, the interplay between biomechanical cues and fibroblast dynamics remains largely unexplored. Here, we investigate how matrix stiffness alters fibroblast transcriptional state and influences lineage specification in fibrotic skin. Methods: We employed a collagen I-based 3-dimensional culture system to expose fibroblasts to varying levels of matrix stiffness, followed by RNA sequencing to identify stiffness-responsive gene expression signature. We integrated single-cell RNA sequencing data from SSc and healthy skin samples to identify fibroblast subsets associated with this signature. Spatial transcriptomic analyses were performed to localise these fibroblasts and their associations with the fibrotic niche. Results: Fibroblasts subjected to increased matrix stiffness exhibited a distinct transcriptional signature, amplified in SSc patients and enriched in PI16+ progenitor-like cells within the SFRP2+ fibrotic compartment. Further analysis indicated that PI16+ fibroblasts are predisposed to SFRP2+ COMP+ PU.1+ myofibroblasts differentiation, whereas blocking mechanotransduction by focal adhesion kinase inhibition disrupts this process, suggesting that matrix stiffness is a key driver of this lineage transition. Spatial mapping revealed colocalisation of the PI16+ and COMP+ subsets in extracellular matrix-dense regions, highlighting the functional relevance of this relationship in fibrotic progression. Conclusions: Our findings suggest that increased matrix stiffness promotes fibroblast precursor differentiation into SFRP2+ COMP+ PU.1+ myofibroblasts, thereby sustaining the vicious cycle of persistent fibrosis in absence of inflammatory triggers. These insights reveal new aspects of fibrosis pathogenesis and highlight biomechanical signals as therapeutic targets in SSc.
CRIS-Team Scopus Importer:2025-07-04

Minimally invasive ultrasound-guided biopsy of the common extensor tendon enthesis: a cadaveric study to standardise the technique - Rizzo, Chiara; Coronel, Luis; De Lorenzis, Enrico; Rubortone, Pietro; Möller, Ingrid; Miguel Perez, Maribel; Tur, Carlo; Raimondo, Maria Gabriella; Belmonte, Beatrice; Cancila, Valeria; Ramming, Andreas; Schett, Georg; et al. (RMD Open, 2025)
OBJECTIVE: To develop and validate a minimally invasive ultrasound (US)-guided biopsy technique to collect entheseal tissue from the common extensor tendon (CET) enthesis at the lateral humeral epicondyle. METHODS: Seven sonographers performed a US examination of the CET on six human cadaveric upper limbs to locate the enthesis using an anatomical landmark-based approach. An adapted mini-arthroscopic system was introduced under US guidance to the target site for sample collection. At the end of the procedure, a dye was injected through the guide needle, followed by dissection, to confirm the sampling location. Histology and immunohistochemistry analyses were performed to assess the quality and representativeness of the samples. The reliability of the procedure among operators was evaluated by analysing the rate of successful sampling. RESULTS: 24 samples were collected. The target site to be biopsied was identified as the insertion of the extensor carpi radialis brevis component of the CET. On dissection, the stain used to verify sampling accuracy was confirmed within the defined target area, with no damage to adjacent structures. Histology and immunohistochemistry indicated that most of the samples exhibited characteristics consistent with entheseal tissue (21 out of 24). All participants identified the CET and successfully completed the procedure, demonstrating reliable sample quality across operators. CONCLUSION: We developed a landmark-based approach to perform a minimally invasive full controlled US-guided biopsy of the CET enthesis that showed to be feasible and reproducible. We believe that this standardised, minimally invasive technique will widespread a reliable collection of entheseal tissue for future clinical and translational studies.
CRIS-Team Scopus Importer:2025-05-16
Keywords: Arthritis; Psoriatic; Tendinopathy; Ultrasonography

POS0494 Fear Of Movement Affects Range Of Motion During Repeated Basmi Exercises Assessed By State-Of-The-Art Motion Capture Techniques - Loy, N.; Blazek, V.; Jukic, Elke; Fleischmann, Martha Elisa; Coppers, Birte; Hübner, Julian; Iqbal, M.; Heinrich, Simon; Scheiterer, Eduard; Leyendecker, Sigrid; Greenfield, Julia; Labinski, H.; et al. (Annals of the Rheumatic Diseases, 2024)
Background: Quantification of spinal mobility in chronic axial spondyloarthritis (axSpA) is an important component of disease assessment and is currently assessed using the clinical Bath Ankylosing Spondylitis Metrology Index (BASMI). Functional movement-based outcome measures are dependent on a number of secondary factors and, in particular, the impact of fear of movement on BASMI performance in axSpA patients is currently unknown. Objectives: To investigate the association of range of motion (RoM) for repeated BASMI exercises detected by inertial measurement units (IMU) and optical-measurement system (OMS) motion capture with fear of movement by Tampa Scale of Kinesophobia 17 (TSK) [1)] in axSpA patients. Methods: AxSpa patients (Internal Medicine 3, Universitätsklinikum Erlangen) and healthy controls (HC) were asked to fill out the TSK and BASMI was performed and scored for three repetitions for each task by a trained physician. The BASMI tasks were performed a second time on the same day as the clinical assessment using OMS. Fifty-four retro-reflective markers and 16 IMU devices (myoMOTION by Noraxon, Scottsdale, USA) were placed on defined anatomic sites (Figure 1) and marker motion was detected with 11 infrared cameras (Oqus 7+, Qualisys, Göteborg, Sweden). BASMI values for each task were analysed in distance (cm) or degree of rotation. A correlation matrix was used to assess the relationship between TSK score and BASMI task 5 (lateral neck flexion in degrees) values from the OMS and IMU data, using the Pearson product moment correlation. Exact BASMI values in degrees and clinical BASMI value per group are reported as means ± standard deviation (SD). Results: Fifty participants were included in the study (30 axSpa patients (12/16 male/female, age: 41.9 (SD 12.3), C-reactive protein: 5.2 (13.8) mg/l and visual analog scale (VAS) global: 4.1 (SD 2.7)) and 20 HC (9/11 male/female, age: 28.4 (SD 3.7) and VAS global 0.1 (SD 0.29)). Measurements from two patients were excluded due to failed IMU und OMS data post-processing, resulting in 28 patients for this analysis. Correlation results between the exact BASMI-5 scores (degree of rotation) for each of the three repetitions and the TSK scores are presented in Table 1. AxSpA patients showed a positive, but not significant (p>0.05) correlation between OMS and TSK score, and a positive, significant (p<0.05) correlation between IMU and TSK score data. The correlation remained stable over the three repetitions. For the IMU data, significant correlations with the tendency of higher values over each of the three repetitions for both groups were observed. In contrast, the HC values showed a negative correlation for both the OMS and IMU values with the TSK score. An increase over the three repetitions in the negative correlation can be seen for both measurement systems. Conclusion: Our results suggest positive relationship between fear of movement and cervical movement restriction in axSpa patients. In addition, axSpA patients tended to achieve higher levels of mobility on repetition of exercise than at baseline. This influence of fear of movement on functional outcomes is especially visible in the IMU data for the axSpa patients. In contrast, the relationship between fear of movement and cervical movement tends to be negative for HC, suggesting that in healthy subjects fear of movement assessed over the TSK does not impact the objectively measured cervical mobility. Further analysis will include a wider range of BASMI tasks to identify movements that might be particularly prone to impairments due to fear of movemen

Real-world usage of digital health applications (DiGA) in rheumatology: results from a German patient survey. - Labinsky, Hannah; Gupta, Latika; Raimondo, Maria Gabriella; Schett, Georg; Knitza, Johannes (Rheumatology International, 2023)
Mobile health applications and digital therapeutics (DTx) aim to improve current patient care. Real-world data on DTx are, however, scarce. The aim of this study was to evaluate the adherence, acceptance, and efficacy of DTx in a clinical routine rheumatology setting. We conducted a prospective observational cohort study assessing the use, adherence, acceptance, and efficacy of the DTx DiGA (Digitale Gesundheitsanwendungen) by survey over 12 weeks. Patients included had to have a rheumatic disease and had been prescribed a DiGA. Acceptance was assessed using the Net promoter score (NPS). 48 patients were prescribed DiGA. Of these, 39/48 (81%) completed the follow-up survey. 21/39 (54%) patients downloaded the DTx and 20/39 (51%) used the DTx at least once. 9/39 (23%) of patients stopped quickly afterward and 5/39 (13%) reported having completed the whole DTx program. Lack of time and commitment were reported as the main reasons for non-use. Overall acceptance of DiGA was high (Net promoter score (NPS) mean (SD) 7.8/10 (2.3)). While the majority of patients (60%) reported no improvement, one subgroup of patients (7/20, 35%) who regularly used an exercise-based DTx for back pain reported symptom improvement. Acceptance of DTx in patients with rheumatic diseases is high, however onboarding to DTx use and adherence to DTx is still challenging in patients with rheumatic diseases. In a subgroup of patients with back pain, however, the use of an exercise-based DTx led to symptom improvement.
EVALuna2:520653

Response to the correspondence on “CD19-CAR T-cell therapy induces deep tissue depletion of B cells” - Tur, Carlo; Eckstein, Markus; Schett, Georg; Raimondo, Maria Gabriella (Annals of the Rheumatic Diseases, 2025)
CRIS-Team Scopus Importer:2025-05-23

Single-cell multi-omics analysis of COVID-19 patients with pre-existing autoimmune diseases shows aberrant immune responses to infection - Barmada, Anis; Handfield, Louis François; Godoy-Tena, Gerard; de la Calle-Fabregat, Carlos; Ciudad, Laura; Arutyunyan, Anna; Andrés-León, Eduardo; Hoo, Regina; Porter, Tarryn; Oszlanczi, Agnes; Richardson, Laura; Calero-Nieto, Fernando J.; et al. (European Journal of Immunology, 2023)
In COVID-19, hyperinflammatory and dysregulated immune responses contribute to severity. Patients with pre-existing autoimmune conditions can therefore be at increased risk of severe COVID-19 and/or associated sequelae, yet SARS-CoV-2 infection in this group has been little studied. Here, we performed single-cell analysis of peripheral blood mononuclear cells from patients with three major autoimmune diseases (rheumatoid arthritis, psoriasis, or multiple sclerosis) during SARS-CoV-2 infection. We observed compositional differences between the autoimmune disease groups coupled with altered patterns of gene expression, transcription factor activity, and cell–cell communication that substantially shape the immune response under SARS-CoV-2 infection. While enrichment of HLA-DRlow CD14+ monocytes was observed in all three autoimmune disease groups, type-I interferon signaling as well as inflammatory T cell and monocyte responses varied widely between the three groups of patients. Our results reveal disturbed immune responses to SARS-CoV-2 in patients with pre-existing autoimmunity, highlighting important considerations for disease treatment and follow-up.
CRIS-Team Scopus Importer:2023-10-27
Keywords: Autoimmunity; COVID-19; Multiple sclerosis; Psoriasis; Rheumatoid arthritis

Stepwise asynchronous telehealth assessment of patients with suspected axial spondyloarthritis: results from a pilot study - Labinsky, Hannah; von Rohr, Sophie; Raimondo, Maria Gabriella; Bohr, Daniela; Morf, Harriet; Horstmann, Britta; Seese, Felix; Seese, Felix; Proft, Fabian; Muehlensiepen, Felix; Boy, Katharina; Kuhn, Sebastian; et al. (Rheumatology International, 2023)
Patients with axial spondyloarthritis (axSpA) suffer from one of the longest diagnostic delays among all rheumatic diseases. Telemedicine (TM) may reduce this diagnostic delay by providing easy access to care. Diagnostic rheumatology telehealth studies are scarce and largely limited to traditional synchronous approaches such as resource-intensive video and telephone consultations. The aim of this study was to investigate a stepwise asynchronous telemedicine-based diagnostic approach in patients with suspected axSpA. Patients with suspected axSpA completed a fully automated digital symptom assessment using two symptom checkers (SC) (bechterew-check and Ada). Secondly, a hybrid stepwise asynchronous TM approach was investigated. Three physicians and two medical students were given sequential access to SC symptom reports, laboratory and imaging results. After each step, participants had to state if axSpA was present or not (yes/no) and had to rate their perceived decision confidence. Results were compared to the final diagnosis of the treating rheumatologist. 17 (47.2%) of 36 included patients were diagnosed with axSpA. Diagnostic accuracy of bechterew-check, Ada, TM students and TM physicians was 47.2%, 58.3%, 76.4% and 88.9% respectively. Access to imaging results significantly increased sensitivity of TM-physicians (p < 0.05). Mean diagnostic confidence of false axSpA classification was not significantly lower compared to correct axSpA classification for both students and physicians. This study underpins the potential of asynchronous physician-based telemedicine for patients with suspected axSpA. Similarly, the results highlight the need for sufficient information, especially imaging results to ensure a correct diagnosis. Further studies are needed to investigate other rheumatic diseases and telediagnostic approaches.
CRIS-Team Scopus Importer:2023-07-07
Keywords: Diagnosis; Health service research; Spondyloarthritis; Symptom checker; Telehealth; Telemedicine

TEMPORAL MIGRATION OF IMMUNE CELLS FROM PSORIATIC SKIN TO JOINTS INITIATING SYNOVIAL INFLAMMATION IN PSORIATIC ARTHRITIS - Raimondo, Maria Gabriella; Rauber, Simon; Xu, Cong; Mohammadian, Hashem; Vogg, Mario; Anchang, Charles Gwellem; Rigau, Aleix; Luber, M.; Labinsky, Hannah; Soare, A.; Distler, Jörg; Fearon, U.; et al. (ANNALS OF THE RHEUMATIC DISEASES, 2022)
CRIS-Team WoS Importer:2022-11-04

The Potential of OMICs Technologies for the Treatment of Immune-Mediated Inflammatory Diseases - Anchang, Charles Gwellem; Xu, Cong; Raimondo, Maria Gabriella; Atreya, Raja; Maier, Andreas; Schett, Georg; Zaburdaev, Vasily; Rauber, Simon; Ramming, Andreas (International Journal of Molecular Sciences, 2021)
Immune‐mediated inflammatory diseases (IMIDs), such as inflammatory bowel diseases and inflammatory arthritis (e.g., rheumatoid arthritis, psoriatic arthritis), are marked by increasing worldwide incidence rates. Apart from irreversible damage of the affected tissue, the systemic nature of these diseases heightens the incidence of cardiovascular insults and colitis‐associated neo-plasia. Only 40–60% of patients respond to currently used standard‐of‐care immunotherapies. In addition to this limited long‐term effectiveness, all current therapies have to be given on a lifelong basis as they are unable to specifically reprogram the inflammatory process and thus achieve a true cure of the disease. On the other hand, the development of various OMICs technologies is consid-ered as “the great hope” for improving the treatment of IMIDs. This review sheds light on the pro-gressive development and the numerous approaches from basic science that gradually lead to the transfer from “bench to bedside” and the implementation into general patient care procedures.
CRIS-Team Scopus Importer:2021-07-30
Keywords: Advanced imaging technologies; Immune‐mediated inflammatory diseases (IMIDs); Single‐cell RNA sequencing; Spatial sequencing